Analysis of small holes manufacturing for optomechanical components - Podaný, Jan; Tomíček, Jan (Manufacturing Technology Journal, 2020)
Small holes can be manufactured by several ways. It is important to define in what dimensions the small holes vary. Anyway, drilling is one of the oldest technologies of holes manufacturing. In small dimensions we use the term microdrilling for description. Beside this conventional way of manufacture there are also unconventional methods. Microdrilling bits very often break before they are worn. Therefore, the tool life of these bits its quite unexpectable. It is due to relatively high load against the drill bit strength. So, it is important to choose proper drill bit material, cutting geometry, construction, process liquid, clamping and cutting conditions. These parameters are import for achieving ideal conditions for microdrilling. Even a tiny change in pre-seted parameters can lead to destruction of these delicate tools. Fiber arrays are designed and manufactured for precise positioning of optical fibers in row (1D) or in plate (2D). Fiber arrays can contain most of fibers including polarization maintaining fibers (PMF).
Keywords: microdrilling; microdrilling bit; optomechanics; fiber array